Interface modification of CH3NH3PbI3/PCBM by pre-heat treatment for efficiency enhancement of perovskite solar cells - Sutthana S. (2017)
© 2017 Elsevier B.V. An interfacial modification of CH 3 NH 3 PbI 3 /PCBM is investigated by pre-heating PCBM solution before spin-coating on the CH 3 NH 3 PbI 3 layer.By adjusting PCBM concentration, PCBM films were optimized to form homogeneous films. Besides, the pre-heat treatment of PCBM solution exhibits a better covered area over CH 3 NH 3 PbI 3 layer with reduced pinhole compared with the non-heat treatment. This can be explained by the higher thermal energy PCBM molecules of the pre-heat solution leading to higher molecule mobility that can reorganizes a structural as well as enhance the diffusion and enhance coverage of PCBM films over CH 3 NH 3 PbI 3 . The optimized cell is enhanced with average power conversion efficiency from 4.59% up to 5.76% (6.44% maximum) by heat treatment. To investigate interface between CH 3 NH 3 PbI 3 and PCBM, the contact angle was measured and found that the contact angle of PCBM films were higher after heat treatment suggesting re-alignment and better orientation of PCBM on perovskite film. The better orientation of PCBM can be explained in term of hydrophilic/hydrophobic property of the interface between CH 3 NH 3 PbI 3 and PCBM. These results suggest that pre-heat treatment of PCBM solution has ability to modify the interface for better orientation of PCBM and resulting in efficiency enhancement due to better carrier transport direction at the CH 3 NH 3 PbI 3 /PCBM interfaces for perovskite solar cells. In addition, the better orientation that the head (non-polar)is oriented at outer surface can also prevent the solar cells from surrounding moisture.